IMPLEMENTASI NILAI-NILAI TRI HITA KARANA PADA BIDANG USAHA PENGGEMUKAN SAPI DI DESA BLUMBANG - I.G Suka; NM. Wiasti; N. Suarsana; IN.S. Miwada (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
This Community service was carried out in the village Blumbang, sub Kerambitan, Tabanan on Saturday,September 22nd, 2012 at 15:00 to 17:00 pm. The participants included members of the village community ofBlumbang who joined in the cattle ranchers. From discussions with the members of the group , it can be saidthat they have a grasp of the concept of THK (Tri Hita Karana) but almost 100% of the participants attendingthis activity have not yet known how to implement. Activities continued with the introduction of fermentationtechnology to solve the problem. All the participants were very enthusiastic. Conclusion could be drawn that theintroduction of THK concept activities and its implementation in their daily life of the village community hasopened Blumbang villagers’ minds. Insight into the importance of processing the feces and urine of cow breedingis as a real form of the THK concept application